Health promotion by International Olympic Sport Federations: priorities and barriers. Issue 17 (15th March 2019) - Mountjoy, Margo; Junge, Astrid; Budgett, Richard; Doerr, Dominik; Leglise, Michel; Miller, Stuart; Moran, Jane; Foster, Jeremy
Abstract : Objective: To identify changes in International Federations' priorities and the barriers to implementing athlete and global health initiatives. Results should influence the work of the International Federation medical committees, the IOC and the Association of Summer Olympic International Federation. Methods: The 28 Summer and 7 Winter International Federations participating in the most recent Olympic Games (2016; 2018) were surveyed to (i) identify the importance of 27 health topics, (ii) assess their progress on implementation health-related programmes and (iii) the barriers to implementation of these programmes. We compared International Federations' activities in 2016 and 2017. Results: The response rate was 83%. Health topics which most International Federations regarded as important and in which the International Federations felt insufficiently active were ' team physician certification ', ' prevention of harassment and abuse ', ' eating disorders/disordered eating ', ' mental health ' and ' injury surveillance '. Compared with 2016, there was a decrease in International Federations' activities in ' injury surveillance ', ' nutritional supplements ' and ' hyperandrogenism '. The main barrier to implementing health-related programmes was ' International Federation political support/willingness ', followed by ' knowledge '. ' Time ' and ' coach support ' were more often reported than ' finances ', or ' IOC or Association of Summer Olympic International Federations partnership '. Conclusion: If International Federations are going to promote health of athletes and global health promotion through physical activity (sport), International Federation leadership must change their focus and provide greater political support for related initiatives. Improving coach and athlete knowledge of the health issues could also facilitate health programme delivery. Time constraints could be mitigated by sharing experiences among the International Federations, Association of Summer Olympic International Federations and the IOC. International Federations should focus on those health-related topics that they identified as being important, yet rate as having insufficient activity.